A 10 mK hermetic cell for eliminating parasitic heating in cryogen-free dilution refrigerators. (September 2020) - Schmoranzer, David; Kumar, Sumit; Triqueneaux, Sébastien; Liu, Xiao; Metcalf, Thomas; Jernigan, Glenn; Collin, Eddy; Fefferman, Andrew
Highlights: Cryogen-free dilution refrigerators often simplify low temperature research. But parasitic heating is generally worse than in wet fridges. As a result, special measures are required to shield nanoelectronic devices. Our mechanical resonator didn't cool to 10 mK without a cryogenic hermetic shield. A 10 mK hermetic shield yielded excellent thermalization of our sample. Abstract : Abstract: Cryogen-free dilution refrigerators generally simplify low temperature research but some types of samples, including superconducting qubits and other nanoelectronic devices, are affected by environmental heat sources such as stray photons or residual helium. We present the design and performance of a hermetic cell installed on the mixing chamber plate of a cryogen-free dilution refrigerator. The performance was quantified by measuring the dependence of the resonance frequency of a mechanical oscillator installed inside the cell on the mixing chamber temperature down to 10 mK. We found the expected logarithmic temperature dependence of the resonance frequency down to the lowest temperatures, demonstrating that the efficiency of the hermetic shield is significantly better than that of a simpler shield with no visible gaps.